ANALYSIS OF LEADERSHIP STYLE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PDAM TIRTA JENEBERANG GOWA REGENCY - Rahmawati; Eka Fitra Ramadani (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study is a quantitative research aimed at determining the effect of leadership style and work discipline on employee performance at PDAM Tirta Jeneberang in Gowa Regency. The sample was taken from PDAM Tirta Jeneberang in Gowa Regency. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the issues under study. The sampling technique used in this study was the Slovin formula. The sample processed in this study consisted of 80 people. Data collection was carried out by distributing questionnaires. In this study, the data sources used in data collection included primary and secondary data. The research instrument used in this study was the Likert scale method. The results of the study were processed using the Statistical Package for the Social Sciences (SPSS) version 27 application. Based on the results of the study, it was found that leadership style and work discipline had a positive and significant effect on employee performance.